Analysis of Determinants of Labor Absorption in Small and Medium Enterprises of Weaving Craft Industry in Sukarara Village, Lombok Tengah - Muhamad Wahyudi; Satarudin, Satarudin; Gusti Ayu Arini (Tinta Emas Institute, 2024)
This study aims to analyze the determinants of labor absorption in small and medium enterprises of the weaving craft industry in Sukarara Village, Jonggat District, Central Lombok Regency. The research is quantitative, involving a population of 40 woven fabric handicraft entrepreneurs in Sukarara Village. Data collection techniques included interviews, documentation, and distributing questionnaires containing questions about work culture, employee performance, and service quality. The analytical tool used was multiple linear regression analysis. The results of the data analysis show that capital and production value have a positive and significant effect on labor absorption in Sukarara Village, Jonggat District, Central Lombok Regency. Wages have a positive but insignificant effect on labor absorption. However, when considered together, capital, production value, and wages have a significant effect on labor absorption in the region.